Mapping the evidence regarding school-to-work/university transition and health inequalities among young adults: a scoping review protocol - Nico Dragano; Benjamin Wachtler; L Sundmacher; Bernd Richter; Stephanie Hoffmann; Max Herke; Claudia Pischke; Katharina Diehl; Marvin Reuter; Paula Mayara Matos Fialho (BMJ Open)
Introduction School-to-work/university transition is a sensitive period that can have a substantial impact on health and health behaviour over the life course. There is some indication that health and health behaviour is socially patterned in the age span of individuals in this transition (16–24 years) and that there are differences by socioeconomic position (SEP). However, evidence regarding this phenomenon has not been systematically mapped. In addition, little is known about the role of institutional characteristics (eg, of universities, workplaces) in the development of health and possible inequalities in health during this transition. Hence, the first objective of this scoping review is to systematically map the existing evidence regarding health and health behaviours (and possible health inequalities, for example, differences by SEP) in the age group of 16–24 years and during school-to-work transition noted in Germany and abroad. The second objective is to summarise the evidence on the potential effects of contextual and compositional characteristics of specific institutions entered during this life stage on health and health behaviours. Third, indicators and measures of these characteristics will be summarised.Methods and analysis We will systematically map the evidence on health inequalities during school-to-work-transitions among young adults (aged 16–24 years), following the methodological framework proposed by Arksey and O’Malley. The literature search is performed in Ovid MEDLINE, Web of Science, International Labour Organization and National Institute for Occupational Safety and Health, using a predetermined search strategy. Articles published between January 2000 and February 2020 in English or German are considered for the review. The selection process follows a two-step approach: (1) screening of titles and abstracts, and (2) screening of full texts, both steps by two independent reviewers. Any discrepancies in the selection process are resolved by a third researcher. Data extraction will be performed using a customised data extraction sheet. The results will be presented in tabular and narrative form.Ethics and dissemination Ethical approval is not required for this scoping review. The results will be published in a peer-reviewed scientific journal and presented at international conferences and project workshops.